2021
DOI: 10.1002/rmv.2231
|View full text |Cite
|
Sign up to set email alerts
|

Neutralising antibody escape of SARS‐CoV‐2 spike protein: Risk assessment for antibody‐based Covid‐19 therapeutics and vaccines

Abstract: Summary The Spike protein is the target of both antibody‐based therapeutics (convalescent plasma, polyclonal serum, monoclonal antibodies) and vaccines. Mutations in Spike could affect efficacy of those treatments. Hence, monitoring of mutations is necessary to forecast and readapt the inventory of therapeutics. Different phylogenetic nomenclatures have been used for the currently circulating SARS‐CoV‐2 clades. The Spike protein has different hotspots of mutation and deletion, the most dangerous for immune esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
170
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(185 citation statements)
references
References 248 publications
(188 reference statements)
3
170
0
1
Order By: Relevance
“…The recent emergence of variants of SARS-CoV-2 with multiple mutations poses a direct threat to the viability of vaccine-based suppression strategies for the pandemic 26 This work, along with other recent findings on the stochastic nature of SARS-CoV-2 transmission 24 , suggests strategies that can be used to suppress the emergence of these fitter viral variants, thereby slowing the evolution of SARS-CoV-2. First, long-term SARS-CoV-2 infections (lasting longer than 30 days) should be treated as a serious public health concern, regardless of the presence of symptoms.…”
Section: Discussionmentioning
confidence: 76%
“…The recent emergence of variants of SARS-CoV-2 with multiple mutations poses a direct threat to the viability of vaccine-based suppression strategies for the pandemic 26 This work, along with other recent findings on the stochastic nature of SARS-CoV-2 transmission 24 , suggests strategies that can be used to suppress the emergence of these fitter viral variants, thereby slowing the evolution of SARS-CoV-2. First, long-term SARS-CoV-2 infections (lasting longer than 30 days) should be treated as a serious public health concern, regardless of the presence of symptoms.…”
Section: Discussionmentioning
confidence: 76%
“…11,14,15 In contrast, many of the other monoclonal antibodies being developed for Covid-19 bind to the receptor-binding motif that engages the angiotensin-converting enzyme 2 (ACE2) receptor and is one of the most mutable and immunogenic regions of the virus; in some cases, these antibodies do not retain activity against the variants. [16][17][18][19] Sotrovimab contains a two-amino acid Fc modification (termed LS) to increase half-life and potentially improve bioavailability in the respiratory mucosa through enhanced engagement with the neonatal Fc receptor. [20][21][22] This modification potentially allows therapeutic concentrations for longer durations.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a plethora of studies has demonstrated antibody evasion for some of the novel VOCs. [19][20][21][22][23][24][25][26][27][28] However, data correlating immune evasion of SARS-CoV-2 VOCs with binding free energies are currently not available. In order to evaluate the thermodynamics contribution of such low cross-reactivity, we calculated the variation in binding free energy values for a selected set of SARS-CoV-2 VOCs RBDs complexed to 21 known nAbs for which atomic coordinates were made publicly available (Table S2).…”
Section: Resultsmentioning
confidence: 99%